1997
DOI: 10.1210/endo.138.4.5038
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Increases Lipogenesis in 3T3-L1 and Human Adipose Cells*

Abstract: Angiotensin II (Ang II) is one of numerous hormones recently shown to be synthesized and secreted by adipose cells. Although the function of Ang II in adipose tissue is unknown, several studies indirectly suggest that it may be involved in control of adiposity. Little is known, however, about direct actions of Ang II in adipose cells. To further investigate this issue, we first characterized the type of Ang II receptors in 3T3-L1 adipocytes. We then tested the hypothesis that Ang II exerted direct actions on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
66
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(71 citation statements)
references
References 28 publications
3
66
0
1
Order By: Relevance
“…1d) during adipocyte differentiation. These findings were consistent with those of Jones et al [13] but not Mallow et al [25]. The apparent difference might be due to the length of experimental period.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…1d) during adipocyte differentiation. These findings were consistent with those of Jones et al [13] but not Mallow et al [25]. The apparent difference might be due to the length of experimental period.…”
Section: Discussionsupporting
confidence: 92%
“…Since that time, mRNA and proteins of the Ang II-forming enzymes in the RAS, including renin and ACE1, have been identified in various rodent or human adipocyte studies [22,23], while Ang II was shown to have effects on human adipose conversion and gene expression of RAS [24]. Jones et al showed that Ang II increased lipogenesis through AT2R in 3T3-L1 adipocytes [13], while another study by Mallow et al detected AT1 receptor proteins throughout the 12-day developmental period of 3T3-L1 cells [25]. Other in vivo studies in mice also reported that AT1R was the predominant Ang II receptor during adipogenesis [15,17], while others found AT2R to predominate [14,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Angiotensin II promoted lipid synthesis and storage in adipocytes [16], produced vasoconstriction and inhibited lipolysis in adipose tissue [17]. Stimulation of the mucosal afferent nerves in the gut produced peripheral vasoconstriction mediated by activation of the renin-angiotensin system [18].…”
Section: Discussionmentioning
confidence: 99%
“…The most-studied genes are those responsible for the control of adipose tissue metabolism and energy balance. For example, fat mass and obesity-associated (FTO) genes are related with weight gain and obesity during childhood [4,8,12,13].…”
Section: Introductionmentioning
confidence: 99%